The Effect of Stock Return Sequences on Trading Volumes - Andrey Kudryavtsev (International Journal of Financial Studies, 2017)
The present study explores the effect of the gambler’s fallacy on stock trading volumes. I hypothesize that if a stock’s price rises (falls) during a number of consecutive trading days, then the gambler’s fallacy may cause at least some of the investors to expect that the stock’s price “has” to subsequently fall (rise), and thus, to increase their willingness to sell (buy) the stock, resulting in a stronger degree of disagreement between the investors and a higher-than-usual stock trading volume on the first day when the stock’s price indeed falls (rises). Employing a large sample of daily price and trading volume data, I document that following relatively long sequences of the same-sign stock returns, on the days when the sign is reversed, the trading activity in the respective stocks is abnormally high. Moreover, average abnormal trading volumes gradually and significantly increase with the length of the preceding return sequence. The effect is slightly more pronounced following the sequences of negative stock returns, and remains significant after controlling for other potentially influential factors, including contemporaneous and lagged actual and absolute stock returns, historical stock returns and volatilities, and company-specific events, such as earnings announcements and dividend payments.